ISOLATION AND CHARACTERIZATION OF CARBOXYLATED NANOCELLULOSE FROM BANANA PEEL FIBER WITH OXIDATION METHOD USING AMMONIUM PERSULFATE - BUDI NUGRAHA - NIM: 23315301, ASHARI
In this study, banana peel from ambon lumut (Musa acuminata triploid AAA) is used as source for carboxylated nanocellulose. Nanocellulose was isolated with oxidation method using ammonium persulfate (APS). In order to investigate the effect of temperature towards the characteristics of nenocellulose, temperature for oxidation process was set at three different values: 60 °C, 70 °C, dan 80 °C. Nanostructure of cellulose is observed as a mix of fiber and whisker from transmission electron microscopy (TEM) images. The diameter of nanocellulose ranging from 12,1 to 25,1 nm. Data from spectrometry graphs (FTIR) confirm existence of carboxyl functional groups in nanocellulose samples. X-ray diffraction pattern (XRD) shows that crystallinity index values increase as temperature of oxidation process increases. The highest crytallinity index value of 72,4% is obtained from nanocellulose treated with oxidation temperature of 80 °C. The result of electrophoretic light scattering (ELS) indicates good stability of nanocellulose dispersion in water. This analysis shows banana peel waste as a potential alternative source for carboxylated nanocellulose.